HLA Variants and Inhibitor Development in Hemophilia A: A Retrospective Case-Controlled Study Using the ATHNdataset - McGill, Joseph R.; Simhadri, Vijaya L.; Sauna, Zuben E. (Frontiers in Medicine, 2021)
In hemophilia A (HA) patients, F8 gene-defects as genetic risk-factors for developing inhibitors to Factor VIII have been extensively studied. Here we provide estimates of inhibitor-risk associated with the patient’s Human Leukocyte Antigen (HLA). We used next generation sequencing for high-resolution HLA Class II typing of 997 HA patients. Using inhibitor prevalence reports from the My Life Our Future (MLOF) research repository, we calculated Odds Ratios (OR) for inhibitor development in a multivariate model considering HLA-DRB1/3/4/5, HLA-DPB1, HLA-DQB1, race, F8 pathogenic variant type, and age. Participants with 1 HLA variant (DPB1*02:02) had developed inhibitors at a higher rate while participants with 2 HLA variants (DRB1*04:07; DRB1*11:04) had developed inhibitors at a lower rate. Additionally, patients with missense variants had developed inhibitors at a lower rate and participants with large structural changes (>50bp) had developed inhibitors at a higher rate (both compared to Intron 22 inversion). Using a cohort of participants with a distribution of HLA-DRB1 alleles comparable to that in the North American population we show that the HLA repertoire of a HA patient can be a risk-factor for inhibitor development.